Knowledge, attitude and practice related to sodium intake among health and non-health science students in IIUM Kuantan - Dahalim, Noor Hazmira; Mat Jusoh, Hanapi (International Islamic University Malaysia, 2020)
Introduction: Salt intake among Malaysians is more than the recommended amount set by World Health Organisation (WHO) of 5g per day (equivalent to 2000mg sodium). Similarly, the prevalence of hypertension has also increased over the year. There is need to reduce salt consumption as outlined in Salt Reduction Strategy to Prevent and Control NCD for Malaysia 2015-2020. In order to reduce the salt intake, the underlying factors must be identified. Thus, the aims of this study were to examine knowledge, attitude and practice related to salt intake in adults specifically among students of IIUM Kuantan. Method: This was a cross-sectional study involving 108 students aged 20-25 years old who completed the questionnaire. The questionnaire consists of demographic data, knowledge, attitude and practice (KAP) related to sodium intake. Data was analysed using descriptive frequency and chisquare test was used to compare the KAP regarding sodium intake between health science and non-health science students in IIUM Kuantan. Results: Almost all students have knowledge that high salt intake can cause hypertension, however, many of them did not know the recommended intake of salt per day. The attitude toward importance of lowering salt intake in the diet showed a significant difference between health science and non-health science students (p<0.01). Majority of students never add salt to the foods at the table but they always add it in cooking when they are at home. Conclusion: No differences in the knowledge and practice related to sodium intake except for attitude between health and non-health science students in IIUM Kuantan.